وبائی امراض کی صورت میں اسلامی معاشرہ کا تعامل محدثین وفقہاء کی آراء کی روشنی میں تحقیقی وتنقیدی جائزہ: A Critical Study of The Behavior of Islamic Society in Pandemic Situation in the Light of The Opinion of Muhaddiseen and Fuqaha - Ismail, Muhammad; Dr. Mubashira; Dr. Abdul Ghani (Journal of Quranic and Social Studies, 2024)
This research delves into the Islamic perspective on the responsibilities of Muslims as good citizens during the spread of epidemic diseases, emphasizing the balance between faith in Allah and the importance of precautionary measures. It underscores the foundational belief in Allah’s absolute control over all matters, as stated in the Quran: “No leaf falls but that He knows of it” (Surah Al-Ana’am, 6:59). Health, illness, joy, and adversity all occur by Allah’s decree, and no disease can transfer independently without His will. The study highlights that taking precautions against diseases aligns with Islamic teachings and true tawakkul (trust in Allah). The Prophet ﷺ exemplified this balance by advising: “Tie your camel first, then put your trust in Allah.” This reflects the principle that reliance on Allah does not negate practical steps for protection. The research reconciles two sets of hadiths: those negating the contagious nature of diseases and those advising precautions. The former rejects pre-Islamic notions that diseases transfer independently, while the latter acknowledges that diseases may transfer under Allah’s will and decree. Scholars emphasize that while causes have effects by Allah’s power, He can neutralize these effects at any time. Therefore, precautions against disease are not only permissible but encouraged. The study concludes that Muslims should adopt a balanced approach, taking practical measures to prevent disease transmission while maintaining trust in Allah. This perspective promotes individual responsibility, public health, and a deeper understanding of divine wisdom.